Development of national framework for health status and health system performance indicators in Saudi Arabia - Mohammed Al-Ghamdi; Mohammed AlTamimi; Nahar Al-Azmi; Taghred Al-Ghaith; Farah AlMuaither; Reema AlThunayyan; Farah AlDlaigan; Abdulrahman S. Bazaid; Ahlam AlShehri (Elsevier, 2023)
Background: The global shift to value-based care has highlighted the necessity for performance measurement in healthcare. While the implementation may be incomplete, governments and providers have been moving towards value-based models of care delivery, funding and performance measurement. Objectives: The purpose of this report is to illustrate the steps taken in designing the framework in Kingdom of Saudi Arabia (KSA), using a 4-step approach: Key Input Analysis, Hierarchy Design, Indicator Analysis and Selection, and Indicator Profile Development. Furthermore, it presents a comprehensive view of the indicators collected to measure performance at the level of the Health System and Health Status in KSA and highlights main patient concerns, thus providing an overview of a new, unified national framework. Methods: The methodology entailed examined the following components' remits and roles, reporting mechanisms and channels, and performance indicators across all pertinent National Health agencies (NHA), by conducting a SWOT analysis of each of the components across the ecosystem. Engagement with the Steering Committee members was achieved through research and interviews. Results: A total of 109 indicators were identified, of which 51 were Health Status Indicator Profiles and 58 Health System Indicators. The indicator profiles were developed with consideration of the KSA context in terms of the healthcare ecosystem as it stands today. The findings of this report, alongside the best practices arising from the benchmarking, will be key inputs into the design of the National Framework. Conclusion: The regulatory entity has set out to establish a National Framework, which aims to unify performance measurement in KSA from both health system and public health perspectives across all sectors providing healthcare services, based on a list of prioritized KPIs and their complete profiles, outlining the formulae, key responsibilities, and reporting mechanisms pertaining to each one.